2016
DOI: 10.1021/acs.jpca.6b06788
|View full text |Cite
|
Sign up to set email alerts
|

Energetics, Thermodynamics, and Hydrogen Bonding Diversity in Ammonium Halide Clusters

Abstract: Contributions from different intermolecular and interionic forces, as well as variations in bond energies, produce size-dependent variations in the structures of acid-base molecular clusters. In this work the structures and interaction energetics of cluster particles with the nominal formulas (NHX), X = (F, Cl, Br) are predicted using either "mag-walking" sawtooth simulated annealing Monte Carlo calculations or model building, followed by M06-2X or RI-MP2 geometry optimization and single-point energy calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 67 publications
1
17
1
Order By: Relevance
“…Earlier work on these systems revealed that M06-2X optimized structures agreed well with experiments as well as MP2, CCSD­(T), and QCISD calculations for ammonium chloride and bromide clusters . In a subsequent assessment of the reliability and accuracy of 200 density functionals, Mardirossian and Head-Gordon found the most promising overall functional that they tested to be ωB97M-V, a range-separated hybrid meta-GGA with nonlocal correlation, designed using a combinatorial approach.…”
Section: Theoretical Methodsmentioning
confidence: 66%
See 4 more Smart Citations
“…Earlier work on these systems revealed that M06-2X optimized structures agreed well with experiments as well as MP2, CCSD­(T), and QCISD calculations for ammonium chloride and bromide clusters . In a subsequent assessment of the reliability and accuracy of 200 density functionals, Mardirossian and Head-Gordon found the most promising overall functional that they tested to be ωB97M-V, a range-separated hybrid meta-GGA with nonlocal correlation, designed using a combinatorial approach.…”
Section: Theoretical Methodsmentioning
confidence: 66%
“…The correct choice of a functional is, as always, important, and several functionals are considered in the present study. For example, in previous work, we found that the M06-2X method performed well for geometry optimization and reaction energetics studies of fairly large ammonium chloride and ammonium bromide clusters. , In the present work, we primarily use the ωB97M-V method developed by Mardirossian and Head-Gordon but also show evidence that both this functional and the MN15 functional developed by Truhlar and co-workers are good choices for DFT modeling of ammonium fluoride clusters.…”
Section: Theoretical Methodsmentioning
confidence: 87%
See 3 more Smart Citations